What’s wrong with cultural diversity in world archaeology? - Holtorf, Cornelius (2017)
Fil: Fil: Holtorf, Cornelius. Linnaeus University. UNESCO Chair in Heritage Futures. Department of Cultural Sciences; Suecia.